Analisis Dampak Integrasi Data terhadap Kecepatan Pelayanan Publik di Kota Surabaya - Renny Sari Dewi (Jurnal Sistem Informasi, 2018)
Since 2013, through Surabaya Single Window (SSW), the Government of Surabaya City has implemented the innovation of public service (electronic government, e-Government) to integrate residence data to the applicant with domicile of Surabaya. Synergy between information technology and public services, the authors suspect there is positive impact of access speed of e-Government after the integration of population data. A mount of 151 respondents have been surveyed when fill-in the SSW application for technical permissions to capture its response time. The researcher concludes that data integration factor through JSON data service technology can accelerate the process of filling data of population equal to 80.7 percent or equal 56.98 seconds faster. It means, if citizenship data integration is implemented thoroughly, the Public Service Integrated Unit (UPTSA) may be able to receive 2.850 application files per day.